The Influence of Social Support and Financial Management Toward Family Well-being in Early Marriage - Rahmi Yulfa; Tin Herawati (Journal of Family Sciences, 2017)
Aim of this study is to examine the influence of social support and financial management toward family well-being in early marriage. Research was located in Cibeber II village and Karehkel village, Leuwiliang sub-district, Bogor district, West Java. Samples of this study are 60 women from an early marriage family (under 20 years old) whose children are under five years old, and willingly participate in this study. Samples were chosen purposively. Social support were positively significant correlation with financial management, objective well-being and subjective well-being. The factors that affect objective family well-being are per capita income and financial management. On the subjective family well-being, the factor of affect is per capita income and emotional social support